Smart City Policies in Realizing the Quality of Public Services in Yogyakarta City - Raissa Almira Deandra; Achmad Nurmandi; Helen Dian Fridayani (Universitas Pancasakti Tegal, 2024)
Major cities around the world believe in the concept of